A new social parasite in the ant genus Ectatomma F. Smith (Hymenoptera, Formicidae, Ectatomminae) - Feitosa, Rodrigo M.; Hora, Riviane R.; Delabie, Jacques H. C.; Valenzuela, Jorge; Fresneau, Dominique (Zootaxa, 2008)
Ectatomma parasiticum Feitosa & Fresneau, a new ant species socially parasitic on Ectatomma tuberculatum (Olivier), is described from gynes discovered in Apazapan, state of Veracruz, Mexico, and reared in the laboratory. Ectatomma parasiticum is the first social parasite described in the Ectatomminae. This species can be distinguished from its host by morphological and behavioral features characteristic of the inquilines known in other ant subfamilies including reduced size, thickened petiole, and agonistic interactions with host species.